Analysis of Corrosion Rate on Cessna 420 Upper Wing (Aluminum Alloy 2024-T3) with Lime Peel Extract and Sodium Chromate Inhibitors in Marine Air at the Polytechnic Aviation Hangar in Makassar - Louis Latif, Hendri; Rossydi, Ahmad; Octavianie, Adhitya; Clara L., Rosalina (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Corrosion in aircraft materials, particularly in wing structures, poses significant challenges to maintenance, especially in environments containing sea air. This study analyzes the corrosion rate on the upper wing of a Cessna 420, made of Aluminum Alloy 2024-T3, using two corrosion inhibitors: sodium chromate (chemical) and lime peel extract (natural). The experiment was conducted over 21 days using the weight loss method in a simulated sea air environment. Scanning Electron Microscopy (SEM), tensile testing, and bending tests were performed to evaluate surface morphology and mechanical properties. Results indicated that both inhibitors effectively reduced corrosion, with sodium chromate providing a more uniform protective layer and showing superior performance in mechanical tests. Lime peel extract, although less effective in terms of surface protection, demonstrated better tensile strength. These findings suggest that lime peel extract could serve as an eco-friendly alternative for corrosion inhibition in aerospace applications.